From Privacy to Exploitation: A Victimological Analysis of Cases Involving the Non-Consensual Distribution of Intimate Content - Yuliani Finaly Putri; Dea Nanda Rahmadani; M Dede Al Farabi Suardi; Denies Salwarani; Ria Anggraeni Utami (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of digital technology has made communication easier, but it has also opened up opportunities for new forms of crime, one of which is the non-consensual distribution of intimate content (non-consensual intimate images). This phenomenon is becoming increasingly common and has serious impacts on victims, whether psychologically, socially, or legally. Unfortunately, victims are often blamed, as they are perceived to have contributed to the occurrence of the incident. This study aims to analyze the position of victims in cases of non-consensual dissemination of intimate content using a victimological perspective, particularly through victim typology and modern victimology approaches. The method used is normative juridical, with a conceptual approach and case studies drawn from relevant news reports. The results of the analysis show that the use of classical victimological typologies often has the potential to create bias and reinforce victim blaming, especially in the context of digital crimes. Therefore, a modern victimology approach is considered more relevant, as it places victims as parties who must be protected rather than blamed. In addition, regulations such as the Law on Sexual Violence Crimes have provided a foundation for legal protection, although in practice they still face various challenges